Designing workbook for teaching writing descriptive text based on scientific approach - Indah Pratiwi; Yanti Sri Rezeki (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
This research aims to design workbook based on the scientific approach for teaching writing descriptive text. This research was conducted on the seventh-grade students of SMPN 24 Pontianak. The method of this research is ADDIE (Analysis, Design, Development, Implementation, and Evaluation) with the exclusion of Implementation and Evaluation phases. This material was designed as supplementary material to support the course book used especially in teaching writing of descriptive text. The respondents in this research were the seventh-grade students and an English teacher at SMPN 24 Pontianak. In this research, the researchers found that workbook based on scientific approach fulfilled the criteria of the good book to teach writing descriptive text. The researchers conducted an internal evaluation to see the usability and the feasibility of the workbook. The result of the evaluation is 89%. It showed that the workbook is feasible to be used by students as the supplementary material to support the main course book and help the students improve their writing ability in descriptive text.